Canting Kanaka, Perserving Batam’s Traditional Batik Design Featuring A Seaside Gallery Like No Other - Gladies Imanda Utami R; Devin Tan; Elyn Fransiska; Indah Yunita; Larassaty Vitrian (Universitas Internasional Batam, 2021)
Batik is an important resource in terms of Indonesia’s culture and history. At present, many have forgotten the value that batik holds, the main goal is to preserve the rich and immense cultural elements behind batik while presenting it in a modernized fashion, fitting for the taste of the current generation and the older generation alike. Canting Kanaka featuring modern design elements combined with traditional Indonesian batik in an effort to maintain the sustainability of Indonesian batik, especially Batam’s batik designs. This project presents a restaurant, café, and a gallery that is adorned with unique secondary skin and batik elements